The sonic scale of interstellar turbulence - Federrath, Christoph; Klessen, Ralf S.; Iapichino, Luigi; Beattie, James R. (Nature astronomy, 2021)
Understanding the physics of turbulence is crucial for many applications, including weather, industry and astrophysics. In the interstellar medium1,2, supersonic turbulence plays a crucial role in controlling the gas density and velocity structure, and ultimately the birth of stars3-8. Here we present a simulation of interstellar turbulence with a grid resolution of 10,0483 cells that allows us to determine the position and width of the sonic scale (ℓs)-the transition from supersonic to subsonic turbulence.